The Influence of Tourist Attraction, Social Media Marketing, and Electronic Word of Mouth on Visitation Decisions at Batur Natural Hot Spring, Kintamani, Bangli - Ni Ketut Veny Yuliasih; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja (AIBPM Publisher, 2024)
Kintamani, as one of the favorite destinations in Bali, has many tourist attractions that are well-known to both domestic and international travelers. The development of a tourist attraction is closely related to tourists visiting decisions. The aim of this research is to investigate how tourist attractions, social media marketing, and electronic word of mouth impact the decision-making process for visiting Batur Natural Hot Spring in Kintamani, Bangli. This study employs a quantitative approach, utilizing multiple linear regression analysis. It incorporates both qualitative and quantitative data, with a sample of 97 respondents, including both domestic and international tourists who have visited Batur Natural Hot Spring. The analysis is conducted using multiple linear regression techniques. The findings reveal that both collectively and individually, tourist attraction, social media marketing, and electronic word of mouth significantly and positively influence the visiting decisions at Batur Natural Hot Spring. Future research could consider expanding this study by introducing additional variables such as destination image, service scape, and service marketing mix.